2011
DOI: 10.5194/acpd-11-26571-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric aerosol compositions in China: spatial/temporal variability, chemical signature, regional haze distribution and comparisons with global aerosols

Abstract: During 2006 and 2007, the daily concentrations of major water-soluble constituents, mineral aerosol, organic carbon (OC) and elemental carbon (EC) in ambient PM<sub>10</sub> samples were investigated from 16 urban, rural and remote sites in various regions of China, and were compared with global aerosol. A large difference between urban and rural chemical species was found, normally with 1.5 to 2.5 factors higher in urban than in rural sites. Optically-scattering aerosols such as sulfate (~16%), OC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
224
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(234 citation statements)
references
References 80 publications
5
224
1
2
Order By: Relevance
“…All the samples were extracted at an ice-water ultrasonic bath at 0°C for 1.5 hours to avoid the losses of ions. (Zhang et al, 2012b). In order to estimate the primary OC (POC) and secondary OC (SOC), the minimum OC/EC ratio method was used with the following equation (Turpin and Huntzicker, 1995;Castro et al, 1999): SOC = OC -EC × (OC/EC) min (Cao et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the samples were extracted at an ice-water ultrasonic bath at 0°C for 1.5 hours to avoid the losses of ions. (Zhang et al, 2012b). In order to estimate the primary OC (POC) and secondary OC (SOC), the minimum OC/EC ratio method was used with the following equation (Turpin and Huntzicker, 1995;Castro et al, 1999): SOC = OC -EC × (OC/EC) min (Cao et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…excluding organic carbon. It was reported that mineral elements contribute less (0.5%) to PM 2.5 (Zhang et al, 2012b). The ratio of organic matter (OM) to organic carbon (OM: OC) could vary from 1.4 to 2.0 in Beijing (Xing et al, 2013).…”
Section: Characterization Of Chemical Components During Different Polmentioning
confidence: 99%
“…By contrast, when the air gets more humid, aerosol water uptake is getting increasingly important. According to round-year observational data (Zhang et al, 2012) (Ye et al, 2003;Zhang et al, 2013). In Nanjing with lower SNA level but higher RH, SNA induced hygroscopic growth may play the dominant role in the enhancement of aerosol lightabsorbing efficiency.…”
Section: Amplified Dome Effect By Mixing With Scattering Aerosolsmentioning
confidence: 99%
“…In China, haze episodes often occur in developed regions such as the North China Plain (NCP) (Sun et al, 2013;Zhang et al, 2013;Che et al, 2014), the Yangtze River Delta (YRD) (Che et al, 2009;Deng, 2011;Du et al, 2012;Yang et al, 2012;Cheng et al, 2013) and the Pearl River Delta (PRD) (Lü et al, 2009;Yue et al, 2010;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%